Prevalence and Associated Risk Factors of Neonatal Hypoglycemia in Iran: A Systematic Review and Meta-Analysis - Roya Farhadi; Moloud Fakhri; Mahmood Moosazadeh; Melina Ramezanpour; Mohammad Yousofpour (Mazandaran University of Medical Sciences, 2023)
Background: Neonatal hypoglycemia is the most common metabolic abnormality affecting newborns and contributes to increased morbidity and mortality.  Objectives: The present systematic review and meta-analysis aim to explore the prevalence and risk factors associated with neonatal hypoglycemia in Iran. Methods: A systematic search was performed in Iranian and international databases, including SID, MagIran, Barakat Knowledge Network System, PubMed, Scopus, Web of Science, and the Google Scholar search engine searched for relevant articles using valid keywords. The search process was updated until September 28, 2021. Data were analyzed using STATA 14 software, and the significance level for all tests was considered P<0.05.  Results: In 14 reviewed articles with a sample size of 18217, the prevalence of hypoglycemia in Iranian newborns was 29% [95%CI: 21%, 37%, P=0.0001] (64% in boys and 37% in girls). The hypoglycemia prevalence was 67% in infants born via cesarean section compared to 24% in vaginally delivered infants. The lowest and highest prevalence of neonatal hypoglycemia was observed in Mashhad (12%) and Arak (53%), respectively. The most common risk factors for neonatal hypoglycemia in Iran were infant prematurity (61%), septicemia (45%), respiratory distress syndrome (RDS) (26%), small for gestational age (SGA) (26%), maternal diabetes (21%), hypocalcemia (19%), intrauterine growth restriction (IUGR) (9%) and perinatal asphyxia (8%). Conclusions: Neonatal hypoglycemia is very common in Iran, affecting nearly one-third of Iranian newborns. The prevalence of hypoglycemia in boys was almost twice as high as that in girls and 2.5 times higher in infants born by cesarean section than in infants delivered vaginally. Furthermore, prematurity was reportedly the most common risk factor for neonatal hypoglycemia in Iran.